Initiation and Runout of Post‐Seismic Debris Flows: Insights From the 2015 Gorkha Earthquake - Maxwell P. Dahlquist; A. Joshua West (Geophysical Research Letters)
Abstract Post‐seismic debris flows are an important hazard following large earthquakes, propagating destruction downstream from hillslopes where coseismic landslides occur and extending damage for years after shaking stops. Data sets of post‐seismic debris flows are necessary to predict initiation and runout characteristics but are presently scarce. We used satellite imagery supplemented by field observations to compile an inventory of >1,000 debris flows associated with the 2015 Gorkha Earthquake in Nepal. We identified two distinct debris flow types: (1) Material from a coseismic landslide was remobilized in a steep channel during a later monsoon; and (2) a new post‐seismic hillslope failure occurred in saturated conditions and became fluidized and channelized. Runout distance was constrained by channel confluences and may be related to confluence geometry. Unstable landslide debris was largely flushed from steep channels during the first monsoon following the earthquake, and the rate of new hillslope failures tailed off over a few years.